2019
DOI: 10.3389/fimmu.2019.02611
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Antibody-Positive Autoimmune Encephalitis in Southwest China: A Multicenter Study

Abstract: In recent years, as an increasing number of neuronal autoantibodies have been detected and used for clinical diagnosis, clinicians have become more aware of autoimmune encephalitis, causing its reported incidence to trend upward over several years. To date, however, there has been no large-scale epidemiological survey of autoimmune encephalitis in adults and children, and its epidemiological characteristics remain unclear. Six main types of antibodies are detected and used to diagnose autoimmune encephalitis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 30 publications
14
41
0
3
Order By: Relevance
“…Recently, Gu et al reported an epidemiological survey about autoimmune encephalitis (AE) in southwestern China, involving six large general hospitals in Chongqing ( 1 ). Their study revealed the underlying relationship between several factors and disease severity ( 1 ).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Gu et al reported an epidemiological survey about autoimmune encephalitis (AE) in southwestern China, involving six large general hospitals in Chongqing ( 1 ). Their study revealed the underlying relationship between several factors and disease severity ( 1 ).…”
mentioning
confidence: 99%
“…Recently, Gu et al reported an epidemiological survey about autoimmune encephalitis (AE) in southwestern China, involving six large general hospitals in Chongqing ( 1 ). Their study revealed the underlying relationship between several factors and disease severity ( 1 ). Although there have been no large-scale epidemiological investigations of AE in China prior to this report ( 1 ), the conclusions of this research would have been more reliable had the following concerns been addressed.…”
mentioning
confidence: 99%
See 3 more Smart Citations